His dark materials. The complete first season [videorecording (DVD)]. - Keen, Dafne, 2005-; Wilson, Ruth, 1982-; Pullman, Philip, 1946- (Warner Bros. Home Entertainment, 2020)
A young girl is destined to liberate her world from the grip of the Magisterium, which represses people's ties to magic and their animal spirits known as daemons. Based on author Philip Pullman's beloved trilogy.